An Integration of Use of Facebook, Peer Assessment with Blended Learning to Enhance the Writing Skills of Freshmen Engineering Graduates – A Pragmatic Approach - Basha, P. Kousaru; Dr. Y. Suneetha; Prof. V. B. Chitra (The journal of contemporary issues in business and government, 2020)
In India, English language teaching-learning has been taken into different means of advancements, the dawn of technology and digitalization of living atmosphere are the two basic and decisive reasons for such an advancement to have an influence not only on one‟s livelihood but also on teaching learning portions of academic and other studyfacets. The teachers of engineering subjects in general and the teachers of the English language, in particular, are seriously tossed to introduce technology and digital means of teaching-learning into their classrooms. The teachers of English have to be efficient facilitators of digital learning means to their learners. Facebook, a social media tool stand best to be blended into English language learning. This paper focuses on the outcomes of the integration of Facebook and peer review and assessment with blended learning to assist and enhance the English language and writing skills of the freshmen engineering graduates.